The Frontier Hero in the Trajectory of Nepali Politics: PMPD With Bhandari’s Leadership Iconic - Karki, Dhruba (State, Society and Development: PMPD Perspectives, 2025)
Joseph Campbell defines the hero as an extraordinary figure who sacrifices his life for the greater cause of humanity. This paper begins by examining the ideas of hero and heroism, with a special focus on Madan Bhandari’s influential role in shaping political developments in Nepal after the 1990s. It explores Bhandari’s efforts to adapt Marxist principles to Nepal’s unique socio-political context through the development of People’s Multiparty Democracy (PMPD)— an ideology that continues to shape the country’s political trajectory to this day. PMPD not only became the mainstream political ideology in post-1990s Nepal but also succeeded in bringing together liberal democratic parties and hardline leftist fronts. Based on an analysis of available published literature and Bhandari’s speeches, this paper examines his influential leadership, which was instrumental not only in unifying various fragmented leftist factions but also in bridging the gap between opposing leftist and rightist forces. These efforts ultimately contributed to the downfall of the autocratic Panchayat regime and the beginning of a new era of democracy and development in Nepal. The paper highlights Bhandari’s legendary role, portraying him not only as a unifying and principled leader but also as a visionary who helped lay the foundation for a transformed Nepal. The study concludes that Bhandari’s heroic personality, leadership, and vision—embodied in PMPD—contributed to the emergence of various peaceful political movements, culminating in the establishment of the Republic of Nepal under the 2015 Constitution.